The Impact of Using Bukalapak on Profitability and Consumer Service - Fachrurazi Fachrurazi (Cita konsultindo, 2022)
Business actors will undoubtedly want to optimize in all areas in order to increase their company's profitability. One thing that must be done is to establish an advertising system based on electronic media, specifically Bukalapak. A system that simplifies buying and selling transactions for both users and consumers. This article seeks to determine the impact of business actors' use of Bukalapak media on resulting profitability, as well as the impact of Bukalapak on consumer convenience when shopping online. This study used a qualitative strategy in the form of a review article in the field of Bukalapak-based marketing management. Writing scientific articles necessitates the use of qualitative methods as well as literature studies or library research.